Multi-carrier frequency hopping spread spectrum system with girth-six low-density parity-check codes - Farid, Ghani, Prof.; Yahya, A. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's hompage at http://ieeexplore.ieee.org/